Analysis of Language Styles in Raya and the Last Dragon Movie (2021) - Febrianti, Annisa Siska; Asroriyah, Atik Muhimatun; Pratiwi, Berlin Insan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The study, titled “Analysis of Language Styles in Raya and the Last Dragon Movie (2021),” applies Martin Joos' (1976) theory of language styles to explore the linguistic dynamics within the film's dialogue. By examining the use of frozen, formal, consultative, casual, and intimate styles, the research aims to understand how language contributes to character development and narrative progression. The analysis identified a total of 70 instances of language styles across the film, distributed as follows: 1 frozen style, 4 formal style, 25 casual style, 25 consultative style, and 15 intimate style. The findings reveal that the most frequently used language styles are casual and consultative, each appearing 25 times. These styles are predominant in the film, reflecting the characters' need for interaction, information exchange, and relationship building. The study highlights the significance of varying language styles in animated films and their role in enhancing the viewer's understanding of character interactions and plot development